Designing Serious Game as Learning Media of Design Thinking Mindset - Ahmad Syahid Zakaria; Billy Muhammad Iqbal; Danu Hadi Syaifullah (Journal of Games, Game Art, and Gamification, 2019)
In many cases, the concept of design thinking (DT) is only taught as an instance method without deep understanding of its basic concepts. The characteristic of DT itself is abstract and practical so difficult to be articulated. On the other side, serious game (SG) comes as a proven solution that can bring a positive impact on the learning process because it can provide an immersive and enjoyable experience. In general, this research will discuss how to design the most appropriate SG to embed the basic concept of DT and how its influence on DT learning process at the participant`s reaction and learning level. This study discusses comprehensively the design process of SG starting from game model, game framework, design sketch, to final prototype. The output of this design is a series of educative games composed of several aspects of meaning and play to teach the basic concept/mindsets of DT.